Reformas legales al literal a) del art. 48 de la ley orgánica de servicio público, relacionado a la incapacidad en el desempeño de las funciones del servidor público como causal de destitución - Alajo Panoluisa, Miriam Betty (2014)
Summary in accordance with the Constitution of the Republic of Ecuador, the Ecuadorian State guarantees to workers full respect for their dignity, a decent life, pay and fair compensation and the performance of healthy and freely chosen or accepted work. This legal precept is protects both the right workers subject to the labour code as public servants, whose rights are laid down in the organic law of public service. The Norma Suprema, guarantees some principles of the right to work, which have the character of being indispensable, so I can quote the following: the right to work; the freedom to work; the promotion of employment and the Elimination of under-employment and unemployment; the inviolability of the rights; fair remuneration; performing the work in a suitable and conducive, environment that ensures their health, integrity, security, hygiene and w Art 23 of the LOSEP, CITES some rights of public servants, among them we have: to) enjoy stability in its place; (o) maintaining his post when it is has diminished its capabilities by catastrophic diseases and/or duration of your treatment and in case of being unable to continue exercising effectively its cargo can move to play another without that is decreased its compensation except in the case ofelfare; etc. that he is welcome to the mechanisms of social security provided for the purpose. Such an event arises it will host retirement procedure for invalidity and set out in this Act and the social security benefits; and q) receive training and ongoing training by the State, to which the institutions will pay facilities. However despite this legal framework that protects the right to work and the the public servant, I notice that the literal to) article 48 of this law grossly violates these rights, to establish itself as a ground for dismissal to the inability of the proven performance of the functions of the public servant, previous performance evaluation and reporting of the immediate supervisor and the administrative unit of human talent Under this causal in practice there have been a series of abstracts administrative, leaving public servants in total lack legal protection because, I think that it should be analysed thoroughly why the disability affecting the public servant; If by working age or other causes and indeed proceed according to the literal or) of article 23 of the law in question. I also consider that the term disability than if we do a brief analysis, means incapable, inept and incapable, therefore, I believe that this cause of dismissal of the civil servant, must refer to a lack of skills, physical or psychological, or knowledge for the public service, as when the engaged public servant has falsified his curriculum and does not have the qualifications or vocational training to play the position and therefore hired. I think that you should analyze whether public server is unable to because were not trained properly to carry out a specific function. It should be noted that you for entry into the public service, the applicant required to meet a series of requirements such as vocational training or academic preparation and also being declared winner in the contest of merits and opposition, laid down in the organic law of public service, therefore cannot fit such disability, ineptidud or inability to the provision of the public service, if he won that contest; Therefore, it is necessary to regulate related to this legal provision in order to foster labour principles and rights such as the right to work and the job security of public servants, established in the Constitution of the Republic of Ecuador, as well as the organic law of public service.